Aberrant Interaction between Parkinson Disease-associated Mutant UCH-L1 and the Lysosomal Receptor for Chaperone-mediated Autophagy - Kabuta, Tomohiro (American Society for Biochemistry and Molecular Biology, 2008)
Parkinson disease (PD) is the most common neurodegenerative movement disorder. An increase in the amount of α-synuclein protein could constitute a cause of PD. α-Synuclein is degraded at least partly by chaperone-mediated autophagy (CMA). The I93M mutation in ubiquitin C-terminal hydrolase L1 (UCH-L1) is associated with familial PD. However, the relationship between α-synuclein and UCH-L1 in the pathogenesis of PD has remained largely unclear. In this study, we found that UCH-L1 physically interacts with LAMP-2A, the lysosomal receptor for CMA, and Hsc70 and Hsp90, which can function as components of the CMA pathway. These interactions were abnormally enhanced by the I93M mutation and were independent of the monoubiquitin binding of UCH-L1. In a cell-free system, UCH-L1 directly interacted with the cytosolic region of LAMP-2A. Expression of I93M UCH-L1 in cells induced the CMA inhibition-associated increase in the amount of α-synuclein. Our findings may provide novel insights into the molecular links betweenα-synuclein and UCH-L1 and suggest that aberrant interaction of mutant UCH-L1 with CMA machinery, at least partly, underlies the pathogenesis of PD associated with I93M UCH-L1.